2009
DOI: 10.1177/1362480609102879
|View full text |Cite
|
Sign up to set email alerts
|

The relative autonomy of women offenders' decision making

Abstract: The article analyses the accounts of incarcerated females in Israel, examining the extent to which they were active, rational agents making choices regarding their criminality. The theoretical framework underlying this analysis views the criminal decision-making process with the agency/structure nexus. It indicates that the women were actively seeking normative means to satisfy their feelings of belonging, to gain economic benefits and feel safe, and to fulfil normative social expectations. They turned to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…On the one hand, Israeli society is governed by a strong patriarchy, due to the central place of religion in daily life and the country's continuous state of war and dominant discourse of masculinity, which affect both women and men (Levy and Sasson-Levy 2008). On the other hand, Israel has adopted a modern Western lifestyle, in which women formally enjoy equality and freedom in education and the workplace (Ajzenstadt 2009). Furthermore, most of the research regarding gender and accounts published to date has been conducted in the United States and Europe, making it difficult to determine whether and to what extent these results are culturally bound, specifically that scholars has emphasized that the stories of offenders are conditioned by culture and context (Presser 2009;Sandberg 2009).…”
Section: Social Constructionism and The Israeli Social-cultural Gendementioning
confidence: 97%
See 1 more Smart Citation
“…On the one hand, Israeli society is governed by a strong patriarchy, due to the central place of religion in daily life and the country's continuous state of war and dominant discourse of masculinity, which affect both women and men (Levy and Sasson-Levy 2008). On the other hand, Israel has adopted a modern Western lifestyle, in which women formally enjoy equality and freedom in education and the workplace (Ajzenstadt 2009). Furthermore, most of the research regarding gender and accounts published to date has been conducted in the United States and Europe, making it difficult to determine whether and to what extent these results are culturally bound, specifically that scholars has emphasized that the stories of offenders are conditioned by culture and context (Presser 2009;Sandberg 2009).…”
Section: Social Constructionism and The Israeli Social-cultural Gendementioning
confidence: 97%
“…Israel may serve as a fruitful arena for exploration of this issue, due to its hybrid culture context (Ajzenstadt 2009). On the one hand, Israeli society is governed by a strong patriarchy, due to the central place of religion in daily life and the country's continuous state of war and dominant discourse of masculinity, which affect both women and men (Levy and Sasson-Levy 2008).…”
Section: Social Constructionism and The Israeli Social-cultural Gendementioning
confidence: 98%
“…Women are formally granted equality and freedom with respect to education, the law (HalperinKaddari 2004), and welfare (Ajzenstadt and Gal 2001), and are therefore fully eligible to participate in all social institutions. However, Israeli society is strongly governed by patriarchal ideologies, which limits the independence of many women and restricts their choice of participation in various social spheres (Ajzenstadt 2009;Halperin-Kaddari 2004). Furthermore, Israeli society is family-oriented and strongly pro-natalist at both institutional and normative levels (Ivry 2010;Remennick 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of disciplines where structuration theory has been successfully utilised in research, Held and Thompson (1989) identified work in psychology, geography, archaeology, management, accountancy, religion, education, technology, and criminology. Studies found from over two decades closest in topic to this thesis include: work on the housing position of ethnic minorities (Sarre, Phillips, & Skellington, 1989), the development of a theoretical model of Black on Black violence (Marino et al, 1998), an examination of decision making about criminal activity of women in Israel (Ajzenstadt, 2009), a study of the victims of wrongful imprisonment and their experience post-release (Tan, 2010), and studies to understand drug harms and HIV transmission (Rhodes, 2009). All of these studies have successfully used structuration theory (Giddens, 1984) to further understand and theorise about their cohort.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Rather than understanding this group as on the one hand, passive victims of the structural constraints of poverty, disadvantage and limited access to resources, or on the other hand as criminals with a personal responsibility to change their ways by addressing their "criminogenic" or dynamic risk factors, it is possible to expand and reframe the view of the cohort in this study. By utilising structuration theory (Giddens, 1984), the actors can be potentially viewed as active, knowledgeable participants in the process, as well as subjects of their position in the social structure (Ajzenstadt, 2009;Marino, Roscigno, & McCall, 1998). Structuration theory (Giddens, 1984) also assists in understanding that the capacity for knowledgeable, intentional action is not the same as unconstrained choice.…”
Section: Theoretical Approachmentioning
confidence: 99%